Health and socio-economic status over the life course: First results from SHARE Waves 6 and 7 - Axel Börsch-Supan; Johanna Bristle; Karen Andersen-Ranberg; Agar Brugiavini; Florence Jusot; Howard Litwin; Guglielmo Weber (De Gruyter, 2019)
Health in later life is shaped by behavior and policies over the life course and reflects the differences between the societies in which we are ageing. This multidisciplinary book answers questions from all life course phases and its interconnections from a European perspective based on the most recent SHARE data, such as: How is our health related to personality traits and influenced by our childhood conditions and careers? Which role does our social network play? Which impacts of the different health care and societal regimes can we trace at older ages? Which are the differences and similarities across European countries?
Keywords: 330